Percepatan Reformasi Birokrasi Melalui Budaya Keterbukaan Informasi di Daerah Istimewa Yogyakarta - Dewi Amanatun Suryani; Erni Saharuddin (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2021)
Public services in Indonesia have many complaints from the public due to unclear procedures, limited access to information, and inadequate infrastructure. The enactment of the Law on Public Information Disclosure gives the public the right to supervise governance and improve the quality of information management and services within the Public Agency. The DIY Regional Government PPID which has been established since 2013 has not shown good performance. The purpose of this study was to analyze the performance of PPIDs and the factors that influence the acceleration of bureaucratic reform to create a culture of information openness. Performance evaluation is measured based on aspects of productivity, service quality, responsiveness, responsibility, and accountability. Meanwhile, the influencing factors are seen from personal / individual, leadership, team, system, and contextual (situational) factors. This research method uses a qualitative descriptive approach. The data collection technique is done through interviews, observation, and documentation study. An important finding from the performance evaluation results is that PPID productivity and accountability are still low. Meanwhile, factors that hinder performance are limited understanding of PLID, lack of intensity of communication between the Regional Head and Assistant PPIDs and the absence of budget support for PPID. Strategies that need to be carried out include improving the quality of PPID service performance by compiling a community satisfaction index, updating the classification of information regularly, monitoring and evaluation by giving awards and punishment, improving personality and utilizing various social media.